ACT NOW in diabetes and foot assessments: an essential service. (2nd December 2020) - Phillips, Anne; Edmonds, Michael; Holmes, Patrick; Robbie, Jayne; Odiase, Charles; Grumitt, John
Abstract : Due to concerns around foot assessments during the COVID-19 pandemic, the iDEAL group have recommended an acronym – ACT NOW – to help health professionals and people with diabetes to recognise the warning signs that might lead to amputation